BENTUK-BENTUK SAPAAN FILM RAMONA AND BEEZUS DISUTRADARAI OLEH ELIZABETH ALLEN (ANALISIS SOSIOLINGUISTIK) - SAIFUDIN, INDAH INDAH SARI ACEP (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This skripsi is entitled Term of address in the movie Ramona and Beezus directed by Elizabeth Allen (a sociolinguistic analysis). Term of address is the way someone gives address to other people in daily conversation, it also an important aspect in discourse which can not be avoided. The aims of this research are to classify and analyze the term of address in the movie of Ramona and Beezus directed by Elizabeth Allen. The writer uses descriptive method. There are three steps to finish this research. First step is preparation, the writer watched the movie of Ramona and Beezus to find out the data. Second step is data collection, the writer will identify the data by reading the script after downloaded from the internet and give a underline and then write down term of address in the piece of the paper. Third step is data analysis. In classifying and analyzing the data, the writer uses the theory of Ervin-Tripp (1971). The result of this research shows that there are 110 term of address used in the movie Ramona and Beezus directed by Elizabeth Allen. There are four types/Aspects of term of address and there were all term of address found in the movie, they are status, rank, identity, and degree of generation. How are their uses by the characters in the movie are 75 term of address according to the aspects of status, 3 term of address according to the aspects of rank, 6 term of address according to the aspects of identity, and 26 term of address according to the aspects of degree of generation. Â Keywords : Term of address, Sociolinguistics Analysis, Movie Ramona and Beezus